2021
DOI: 10.3389/fimmu.2021.687534
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies and Infection: Non Nova Sed Nove

Abstract: The clinical significance of antiphospholipid antibodies (aPL) in the context of infections has attracted attention since their first discovery in patients with syphilis. In fact, the recognition of aPL in patients with infections has been described in parallel to the understating of the syndrome. Since the first description of aPL-positive tests in three patients with COVID-19 diagnosed in January 2020 in Wuhan, China, a large number of studies took part in the ongoing debate on SARS-2-Cov 2 induced coagulopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 9 publications
(13 reference statements)
1
18
0
1
Order By: Relevance
“…and their presence was associated with thrombosis and severity of COVID-19 (18,(39)(40)(41)(42). However, multiple other studies did not demonstrate either differences between COVID-19 and control populations or clinical associations (33,34,(43)(44)(45)(46). The significantly higher frequency of anti-CL IgM autoantibodies that we found in COVID-19 patients compared to controls was not associated with unfavorable outcomes as previously reported (29).…”
Section: Discussionsupporting
confidence: 77%
“…and their presence was associated with thrombosis and severity of COVID-19 (18,(39)(40)(41)(42). However, multiple other studies did not demonstrate either differences between COVID-19 and control populations or clinical associations (33,34,(43)(44)(45)(46). The significantly higher frequency of anti-CL IgM autoantibodies that we found in COVID-19 patients compared to controls was not associated with unfavorable outcomes as previously reported (29).…”
Section: Discussionsupporting
confidence: 77%
“…1 , 2 , 3 However, some concerns have been raised regarding the safety of the vaccines in patients with antiphospholipid antibodies, as these antibodies have been reported to appear following both infection and vaccination and have been identified in patients with COVID-19. 4 Although a few cases of thrombocytopenia and thrombotic events with clinical features resembling antiphospholipid syndrome have been reported in recipients of either adenoviral vector-based or mRNA-based COVID-19 vaccines, 5 a pathogenic link and, more critically, the clinical relevance of antiphospholipid antibodies in these clinical settings have yet to be fully elucidated.…”
mentioning
confidence: 99%
“…Antiphospholipid antibodies, and particularly anticardiolipin antibody positivity, have been associated with multiple chronic infections including hepatitis C virus (HCV), HIV, syphilis and leprosy, among others 14. These antibodies tend to be transient and not associated with thrombosis 15. Sciascia et al recently found that 49% of patients with a viral or bacterial infection (including T. pallidum, cytomegalovirus and Pseudomonas aeruginosa , among others) and 53% of patients with COVID-19 had antiphospholipid antibodies, although they were unrelated to thrombosis 15.…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies tend to be transient and not associated with thrombosis 15. Sciascia et al recently found that 49% of patients with a viral or bacterial infection (including T. pallidum, cytomegalovirus and Pseudomonas aeruginosa , among others) and 53% of patients with COVID-19 had antiphospholipid antibodies, although they were unrelated to thrombosis 15. IgM antibodies to both cardiolipin and β2 glycoprotein are correlated with lower antiphospholipid scores (and lower risk of thrombosis in APS) than are the respective IgG antibodies 16.…”
Section: Discussionmentioning
confidence: 99%